Organizational Predictors and Use of Evidence-Based Practices in Adolescent Substance Abuse Treatment. Issue 4 (October 2015) - Paino, Maria; Aletraris, Lydia; Roman, Paul M.
Background: Adolescent substance abuse remains a significant problem in the United States, yet treatment centers do not always admit adolescent clients. In this paper, we first determine the extent to which treatment is available for adolescents in general and whether or not adolescent-specific (segregated) tracks are offered. Second, we examine the organizational characteristics associated with adolescent treatment. Third, we illuminate how the adolescent caseload in a treatment center is related to offering evidence-based practices (EBPs). Methods: Drawing upon a nationally representative sample of US treatment programs, we use logistic regression to assess how organizational characteristics are associated with the provision of adolescent treatment. Using ordinal logistic regression, we analyze how the treatment center's adolescent caseload and organizational characteristics affect the extent to which a treatment center offers medication-assisted treatment (MAT) and psychosocial treatment. Results: Half (49.5%) of treatment programs admitted adolescents, and 41.8% offered an adolescent-specific track. Findings from the logistic regression suggested several organizational characteristics that were significantly associated with treating adolescents and/or having an adolescent-only track. Our findings from the ordinal models indicated a negative relationship between the percent of adolescents in a treatment center and the extent of MAT, and a positive relationship between the percent of adolescent clients and the extent of psychosocial treatment offered. Conclusions: This paper highlights organizational barriers to treatment entry for adolescents, who remain a small proportion of clients in treatment centers. When treatment centers serve adolescents, however, those adolescents are likely to receive care in adolescent-only tracks and/or services and in programs that offer several psychosocial EBPs. Finally, adolescents are less likely to receive treatment in centers that offer a variety of MAT.